Fracture zones constrained by neutral surfaces in a fault-related fold: Insights from the Kelasu tectonic zone, Kuqa Depression. (November 2017) - Sun, Shuai; Hou, Guiting; Zheng, Chunfang
Abstract: Stress variation associated with folding is one of the controlling factors in the development of tectonic fractures, however, little attention has been paid to the influence of neutral surfaces during folding on fracture distribution in a fault-related fold. In this study, we take the Cretaceous Bashijiqike Formation in the Kuqa Depression as an example and analyze the distribution of tectonic fractures in fault-related folds by core observation and logging data analysis. Three fracture zones are identified in a fault-related fold: a tensile zone, a transition zone and a compressive zone, which may be constrained by two neutral surfaces of fold. Well correlation reveals that the tensile zone and the transition zone reach the maximum thickness at the fold hinge and get thinner in the fold limbs. A 2D viscoelastic stress field model of a fault-related fold was constructed to further investigate the mechanism of fracturing. Statistical and numerical analysis reveal that the tensile zone and the transition zone become thicker with decreasing interlimb angle. Stress variation associated with folding is the first level of control over the general pattern of fracture distribution while faulting is a secondary control over the development of local fractures in a fault-related fold. Highlights: Three fracture zones are identified in a fault-related fold. A 2D viscoelastic stress field model of a fault-related fold was constructed. Folding plays a crucial role in controlling the general distribution of fractures. Faulting has a local influence on the development of fractures around the fault.